2010
DOI: 10.1007/s00432-010-0820-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of CA 19-9 and CEA in pancreatic cancer-associated diabetes

Abstract: Elevated CEA (≥5 ng/ml) and CA19-9 (≥500 U/ml) levels have an association with diabetic pancreatic cancer. New-onset diabetes combined with higher CA 19-9 and/or CEA might be regarded as a useful tool to screen early pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Furthermore, the serum levels of the tumor markers are even less useful for the diagnosis of PMC [24,25]. Bassi et al [24] found that CEA again seems to be the most accurate indicator for the diagnosis of a mucinous cyst, but with a sensitivity as low as 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the serum levels of the tumor markers are even less useful for the diagnosis of PMC [24,25]. Bassi et al [24] found that CEA again seems to be the most accurate indicator for the diagnosis of a mucinous cyst, but with a sensitivity as low as 17%.…”
Section: Discussionmentioning
confidence: 99%
“…In selected cases where there is clinical suspicion or risk factor of PaC further evaluation should be made with assessment of tumor markers like CA-19-9 and CEA. Both of these markers have shown a positive correlation with PaC-associated diabetes [9].…”
Section: Discussionmentioning
confidence: 96%
“…Cancer antigen (CA) 19–9 is used in the diagnosis of pancreatic cancer but is also a marker of pancreatic tissue damage that might be caused by diabetes. Thus, the diagnosis of new-onset diabetes combined with higher CA 19–9 and/or carcinoembryonic antigen (CEA) might be regarded as a useful tool to screen early pancreatic cancer [80]. …”
Section: Reviewmentioning
confidence: 99%